Phosphor thermometry in an EB-PVD TBC - Steenbakker, Remy (Cranfield University, 2008)
Thermal Barrier Coatings (TBCs) are used to reduce the actual working temperature of the high pressure turbine blade surface. Knowing the temperature across a TBC and at the interface with the thermally grown oxide (TGO) under realistic conditions is highly desirable. As the major life#controlling factors for TBC systems are linked with temperature, this would provide useful data for a better understanding of these phenomena and to assess the remnant life#time of the TBC. This would also enable the design of advanced cooling strategies in the most efficient way using a minimum amount of air. Further the integration of a sensor coating into an on#line temperature detection system will enable the full potential of TBCs to be realised due to improved precision in temperature measurement and early warning of degradation. This in turn will increase fuel efficiency and reduce CO2 emissions. The concept of sensing TBCs was patented by Choy et al. [114] in 1998 and consists of locally modifying the composition of the TBC so that it acts as a thermographic phosphor. As a result, the temperature dependence of the lifetime of the laser induced phosphorescence process can be used for temperature measurements. The purpose of this work was to develop a multilayer sensing TBC deposited by electron beam physical vapour deposition (EB#PVD) which could be used to remotely measure the temperature at different depths in the coating. In this study, the reader is introduced to the theory of luminescence sensing and its TBC application. Several yttria partially stabilised zirconia TBCs, co#doped with rare earth oxides (YSZ:RE) phosphors, were studied and it was shown that dysprosia doped YSZ has the highest temperature sensitivity. The influence of dopant concentration, layering and high temperature aging on the phosphorescence process were also researched. During the project, a novel, non#destructive, method to monitor the high temperature degradation of the TBC using phosphorescence measurements was found. Alternative phosphor compositions, based on yttrium aluminium garnet (YAG) material, were successfully deposited by EB#PVD and it was shown that doped YAG TBC compositions could further improve the maximum temperature measurement capability of current sensing TBCs. A multilayer EB#PVD coating comprising of two different phosphor layers was deposited and tested in order to demonstrate that such systems could be used to remotely measure the temperature at two different depths in the TBC simultaneously and therefore to monitor the thermal gradient in the coating, permitting the direct measurement of heat flux under thermal gradient conditions, for example in service.